Sperm kinematic characterization of alpaca (Vicugna pacos L.) during the reproductive season. (18th August 2018) - Meza, Aydee; Caldeira, Carina; Valverde, Anthony; Ordóñez, César; Ampuero, Enrique; Cucho, Hernán; Soler, Carles
Contents: Semen analysis is a key factor when determining the fertility ability in males. South American camelids, and in particular the alpaca, have been studied very little when compared with other farm animals. The aim of this work was to perform the kinematic characterization of alpaca spermatozoa collected directly from the deferent duct by using CASA‐Mot (Computer Assisted Semen Analysis for Motility) technology. Samples were obtained every three days throughout the reproductive season during two periods and with a break of seven days in the middle. During both periods, the quality of the sample's motility and kinematics increased over the first two days and then subsequently decreased. This pattern was similar in all animals. It was concluded that the introduction of resting times can be useful to improve sperm quality for artificial insemination purposes in natural conditions.